The Effect of Sadaqa Jum’at to Increasing Number of Members in Ranting Muhammadiyah Batunadua & Sitamiang - Fitri Agustina; Sutan Siregar; Iskandar Safri Hasibuan (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2022)
The phenomenon of the lack of group members in Muhammadiyah Batunadua Sitamiang branch was threatening the group's sustainability. One of the related variables in an increasing number of organization members is Sadaqa. This study designs a measuring instrument for Sadaqa an Islamic perspective and looks at its effectiveness in addition to the member of the branch. The research method used in this study is quantitative research, which consists of 2 variables, namely the independent variable regarding the behavior of Sadaqa and the dependent variable regarding the increase in members. Moreover, the data collection technique of the study is through the distribution of questionnaires to 40 members of the Batunadua Sitamiang branch, and interviews and the analysis technique of is the recreation 1 predictor. As the results of this study concluded that there is an influence between Sadaqa behavior and the addition of the number of members in the Batunadua and Sitamiang branches, this is evidenced by the results of the correlation between predictor X and criterion Y using the tangkar moment correlation technique from a person, using the help of Microsoft Excel, the correlation result is r2 = 0, 23789. As well as the correlation significance test through the t using the help of Microsoft Excel, the result is 0.69 for that Friday Sadaqa behavior is a factor that can be used as a predictor in increasing the number of members of the branch. The number of members of the branch should be accompanied by sincere intentions and a pure heart. This research has opened a discussion about the benefits of Sadaqa in an organizational perspective of Muhammadiyah.